Formation of Verbal Forms of Imperative in the Livvik and Lyudik Dialects of Karelian Language - T. V. Pashkova; A. P. Rodionova (Научный диалог)
The question of the formation of imperative forms in the dialects of the Karelian language is considered. Attention is paid to two dialects: Livvik and Lyudik. The results of a comparative analysis of affirmative and negative forms of the imperative in the mentioned adverbs are presented. Particular attention is paid to the indicators of the imperative, their origin, features of use in a comparative aspect. The novelty of research is that at present the literary form of the Lyudik dialect of the Karelian language is still not fully formed, and today the Lyudik dialect is poorly represented in the educational space: systematic and systematic teaching due to the influence of objective and subjective factors is not conducted. It is noted that the Livvik dialect, on the contrary, is actively taught in educational institutions of the Republic of Karelia, the grammatical structure of this dialect is quite well studied and tested in the educational process. Based on the fact that the Livvik and Lyudik dialects are most closely related to each other, the material analyzed can also be used in the preparation of textbooks, which are urgently needed by people of the Lyudik dialect.